The link between local community perception on economic impacts of a tourism development model - Ahmad, Nurul Azwa; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Faculty of Forestry, Universiti Putra Malaysia, 2013)
This article focuses on the identification and explanation of the link between local community perceptions on economic impacts and the model related to tourism development. Many researchers have demonstrated in their past studies about the model related to local community perceptions towards tourism development. This study discusses on local community perceptions on economic impacts related to a model development. This study focuses on local community perceptions on rural tourism development in the Kilim Karst Geopark (KKGP), Langkawi.